Animal Models of Behavioral Analysis - Raber, Jacob; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Despite the difficulty in comparing clinic-based human tests with animal model testing, there is still great value in pursuing translational approaches, as tests and treatment strategies might be developed to improve brain function in humans suffering from neurological conditions and knowledge obtained from human behavioral studies can be used to further improve the animal models of behavioral analysis. In Animal Models of Behavioral Analysis, expert neuroscientists focus on approaches to translate and compare behavioral tests used in animals with those used in humans not only to increase our understanding of brain function across species but also to provide objective performance measures and bridge the gap between behavioral alterations in humans with cognitive disorders and the correlating animal models of these conditions. Written in the Neuromethods series format, the chapters provide authoritative reviews of many commonly used approaches in the field today. Provocative and cutting-edge, Animal Models of Behavioral Analysis seeks to aid researchers in further developing these vital techniques in an effort to advance studies in both the clinic and the laboratory.
Eyeblink Conditioning in Animal Models and Humans -- Anatomical, Physiological, and Behavioral Analysis of Rodent Vision -- Correlates and Analysis of Motor Function in Humans and Animal Models of Parkinson's Disease -- Spatial Learning and Memory in Animal Models and Humans -- Fear Conditioning in Rodents and Humans -- Conditioned Place Preference in Rodents and Humans -- Social Interactions in the Clinic and the Cage: Towards A More Valid Mouse Model of Autism -- The Experimental Manipulation of Uncertainty -- Circadian Variation in the Physiology and Behavior of Humans and Nonhuman Primates -- Traumatic Brain Injury in Animal Models and Humans -- Behavioral Sensitization to Addictive Drugs: Clinical Relevance and Methodological Aspects -- Evaluating Behavioral Outcomes from Ischemic Brain Injury -- A Comparative Analysis of Cellular Morphological Differentiation Within the Cerebral Cortex Using Diffusion Tensor Imaging.
Keywords: Neurosciences; Neurology .; Animal models in research; Neurosciences; Neurology; Animal Models